Investigation on the Effects of Modifying Genes on the Spinal Muscular Atrophy Phenotype - Zhuri, Drenushe; Gurkan, Hakan; Eker, Damla; Karal, Yasemin; Yalcintepe, Sinem; Atli, Engin; Demir, Selma; Atli, Emine Ikbal (Global Medical Genetics, 2022)
Introduction Spinal muscular atrophy (SMA) is an autosomal recessive neuromuscular disorder caused by the degeneration of motor neurons, muscle weakness, and atrophy that leads to infant's death. The duplication of exon 7/8 in the SMN2 gene reduces the clinical severity of disease, and it is defined as modifying effect. In this study, we aim to investigate the expression of modifying genes related to the prognosis of SMA like PLS3, PFN2, ZPR1, CORO1C, GTF2H2, NRN1, SERF1A, NCALD, NAIP, and TIA1.Methods Seventeen patients, who came to Trakya University, Faculty of Medicine, Medical Genetics Department, with a preliminary diagnosis of SMA disease, and eight healthy controls were included in this study after multiplex ligation-dependent probe amplification analysis. Gene expression levels were determined by real-time reverse transcription polymerase chain reaction and delta–delta CT method by the isolation of RNA from peripheral blood of patients and controls.Results SERF1A and NAIP genes compared between A group and B + C + D groups, and A group of healthy controls, showed statistically significant differences (p = 0.037, p = 0.001).Discussion PLS3, NAIP, and NRN1 gene expressions related to SMA disease have been reported before in the literature. In our study, the expression levels of SERF1A, GTF2H2, NCALD, ZPR1, TIA1, PFN2, and CORO1C genes have been studied for the first time in SMA patients.
Keywords: spinal muscular atrophy; modifying genes; neuromuscular disorder; SMN1; SMN2